Nanoscale TiO2 nanotubes govern the biological behavior of human glioma and osteosarcoma cells - Tian A (Dove Medical Press, 2015)
Ang Tian,1 Xiaofei Qin,2 Anhua Wu,2 Hangzhou Zhang,3 Quan Xu,4 Deguang Xing,2 He Yang,1 Bo Qiu,2 Xiangxin Xue,1 Dongyong Zhang,2 Chenbo Dong5 1Liaoning Provincial Universities Key Laboratory of Boron Resource Ecological Utilization Technology and Boron Materials, Northeastern University, 2Department of Neurosurgery, The First Affiliated Hospital of China Medical University, 3Department of Sports Medicine and Joint Surgery, The First Affiliated Hospital of China Medical University, Shenyang, 4Institute of New Energy, State Key Laboratory of Heavy Oil Processing, China University of Petroleum, Beijing, People’s Republic of China; 5Department of Civil and Environmental Engineering, Rice University, Houston, TX, USA Abstract: Cells respond to their surroundings through an interactive adhesion process that has direct effects on cell proliferation and migration. This research was designed to investigate the effects of TiO2 nanotubes with different topographies and structures on the biological behavior of cultured cells. The results demonstrated that the nanotube diameter, rather than the crystalline structure of the coatings, was a major factor for the biological behavior of the cultured cells. The optimal diameter of the nanotubes was 20 nm for cell adhesion, migration, and proliferation in both glioma and osteosarcoma cells. The expression levels of vitronectin and phosphor-focal adhesion kinase were affected by the nanotube diameter; therefore, it is proposed that the responses of vitronectin and phosphor-focal adhesion kinase to the nanotube could modulate cell fate. In addition, the geometry and size of the nanotube coating could regulate the degree of expression of acetylated α-tubulin, thus indirectly modulating cell migration behavior. Moreover, the expression levels of apoptosis-associated proteins were influenced by the topography. In conclusion, a nanotube diameter of 20 nm was the critical threshold that upregulated the expression level of Bcl-2 and obviously decreased the expression levels of Bax and caspase-3. This information will be useful for future biomedical and clinical applications. Keywords: nanotopography, migration, proliferation, adhesion, apoptosis